Barriers to rural women's involvement in economic activities : evidence from Shaanxi, China : a dissertation presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Economics at Massey University, Manawatu, New Zealand - Yang, Mei (Massey University, 2017)
With China’s fast development in urbanization and agricultural modernization, rural women are one of the most affected yet ignored groups in society. However, strong evidence has shown that women’s active economic participation can not only reduce the likelihood of household poverty, but also improve distributional dynamics within a household. With first-hand data collected from three areas in one province, this research studies rural women’s barriers to economic participation in farming and off-farm employment under the government’s policy of land transfer. It is found that rural women are facing different challenges and have diversified needs and aspirations. There is a mismatch between the training local government offered and what rural women really want. The study of women professional farmers aims at building an updated understanding of rural women within the fast pace of China’s modernization. This research covers some of the critical factors of economic growth, such as the role of geography, gender, history and institutions. The findings provide information to policy makers, researchers and social organizations concerned with the future of rural women, and assist the sustainable implementation of the land transfer policy and gender equality.
Keywords: Women in economic development; Rural women; Education; Employment; Women; Social conditions; China; Shaanxi Sheng